Hospital Information System (SIRS) Using Human Model Organization Technology-Fit (Hot-Fit) in Pharmaceutical Installation - Pamungkas, Rian Adi; Thomas Regina Putra; Fransiskus Adikara; Agusdini Banun Saptaningsih (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: The application of information technology systems integrates the entire IFRS service process. Evaluation is needed to find out the benefits of SIRS in IFRS using the Human, Organization, Technology (HOT) Fit evaluation framework Objective: The study aimed to analyze the influence of Human, Organizational, Technology factors on Net Benefit in the Dinda Hospital Pharmacy Installation. Method: This research uses a quantitative approach with a causal research design using PLS SEM. The sample in this study was 30 staff who worked in IFRS. The research instrument uses a questionnaire and is measured using a Likert scale. Result: Based on the results of the t-statistical test, there is a discrepancy that appears in the form of an insignificant direct effect between the influence of information quality on system use (p-value 0.199), information quality on user satisfaction (p-value 0.480), service quality on user satisfaction (p-value 0.276), system quality to structure (p-value 0.414), information quality to structure (p-value 0.431), and environment to net benefit (p-value 0.450). Conclusion. improving the quality of user capabilities can directly influence the quality of the information produced. Quality information can be used directly by organizations in making decisions to fulfill and improve pharmaceutical services at Tangerang Hospital. Recommendation. Further research needs to be conducted with different population sizes and the use of HOT-fit models needs to be maximized by using more complex variables by combining existing methods with methods from another research